Longitudinal Study of the Vocational and High School Graduation Rate from 2011 to 2016 in Erie County, New York - Ilhamdaniah Saleh (Faculty of Engineering, Universitas Negeri Yogyakarta, 2018)
This study highlighted the discrepancies of education outcomes in urban-suburban settings and the differences between the graduates of vocational high schools and general high schools from 2011 to 2016 in Erie County, New York State, United States. Erie was infamous for racial segregation and the discrepancy of school quality between urban, suburban, and rural areas. New York State Department of Education has invested efforts to improve the education outcomes of vocational and high school education in the region. However, the education outcome gap still existed between those schools. The data source was derived from the School Report Card from 2011 to 2016 published by New York State Department of Education. The outcome variable was the percentage of high school graduates who attained Regent diploma (New York State standard) or the graduation rate. Methods utilized were an independent sample t-test, an analysis of variance, and a hierarchical linear model to measure the difference in longitudinal growth of graduation rate from 2011 to 2016. The results showed that there was a significant difference in the means of the graduation rate between vocational and general high schools. Teacher academic qualifications and certifications had a positive relationship with the graduation rate. The implication of this study called for tremendous efforts to improve the educational outcome, leverage teacher competencies, and close the gap.